2014
DOI: 10.1111/pme.12514
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Music in Endoscopy Procedures: Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Our meta-analysis suggested that music may offer benefits for patients undergoing endoscopy, except in colposcopy and bronchoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 60 publications
2
32
0
1
Order By: Relevance
“…The STAI scores at the time of admission were similar in the two groups, whereas a significant difference in the STAI-State score [median (interquartile range, IQR) 35 (18) vs. 43 (25); p =0.03, r =−0.18] was observed between the music and the control group before bronchoscopy, with lower scores in the music group. These differences were no longer seen before discharge, although the scores in both groups were found to be at a lower level [median (IQR) 40 (19) vs. 31 (17), p< 0.0001 and 37 (19) vs. 30 (13); p< 0.0001] (Table 1).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The STAI scores at the time of admission were similar in the two groups, whereas a significant difference in the STAI-State score [median (interquartile range, IQR) 35 (18) vs. 43 (25); p =0.03, r =−0.18] was observed between the music and the control group before bronchoscopy, with lower scores in the music group. These differences were no longer seen before discharge, although the scores in both groups were found to be at a lower level [median (IQR) 40 (19) vs. 31 (17), p< 0.0001 and 37 (19) vs. 30 (13); p< 0.0001] (Table 1).…”
Section: Resultsmentioning
confidence: 85%
“…The authors concluded that music decreases anxiety and heart rate overall, but in a subanalysis found that it had no significant effect regarding bronchoscopy (18). Moreover, a review including just one of the bronchoscopy studies investigating the effect of music on state anxiety scores concluded that music reduces anxiety in normal care delivery but not in unpleasant procedures, such as bronchoscopy (19).…”
mentioning
confidence: 99%
“…Other authors have also demonstrated anxiety reduction in mechanically ventilated ICU patients through music interventions [1517]. Wang et al [18] has indicated that the use of music interventions can significantly improve pain score, anxiety, heart rate, arterial pressure, and satisfaction score for patients undergoing a variety of endoscopic procedures. Notably, Hole et al [19] demonstrated that music can help alleviate postoperative pain, anxiety, and analgesia needs in addition to improving patient satisfaction during recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Music has been acknowledged as a safe and effective non‐pharmacological anxiolytic agent due to its effect on the perception of pain and anxiety reducing the regular pharmacological sedative doses . A recent meta‐analysis on the effect of music during endoscopy procedures has shown a beneficial effect of reducing anxiety and pain in patients undergoing endoscopy procedures, with a possible exception of patients undergoing colposcopy and bronchoscopy . Yet within the realm of pleural procedures, patients’ listening to music as an intervention to reduce pain and anxiety has not been examined.…”
Section: Introductionmentioning
confidence: 99%